2010
DOI: 10.5713/ajas.2010.90481
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic Response to Karaya Saponin and Rhodobacter capsulatus in Broiler Chickens

Abstract: :Dietary karaya saponin and Rhodobacter capsulatus (R. capsulatus) are known to have hypocholesterolemic actions, as reported in our previous studies. This study examined possible synergistic hypocholesterolemic effects of karaya saponin and R. capsulatus in broilers. A total of 150 broilers were allocated into 10 treatments: control, saponin 25 mg, saponin 50 mg, saponin 75 mg, saponin 25 mg+R. capsulatus 0.2 g, saponin 25 mg+R. capsulatus 0.4 g, saponin 50 mg+R. capsulatus 0.2 g, saponin 50 mg+R. capsulatus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
6
7
1
Order By: Relevance
“…In the present study, no changes in serum AST and ALT levels indicate no negative effect of dietary saponins on the liver functioning. In line with these results, no change in serum AST and ALT levels have also been observed in broiler chicken (Afrose et al, ; Gaurav, ) and broiler breeder (Chaudhary, ) due to the supplementation of dietary saponins of different sources.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In the present study, no changes in serum AST and ALT levels indicate no negative effect of dietary saponins on the liver functioning. In line with these results, no change in serum AST and ALT levels have also been observed in broiler chicken (Afrose et al, ; Gaurav, ) and broiler breeder (Chaudhary, ) due to the supplementation of dietary saponins of different sources.…”
Section: Discussionsupporting
confidence: 68%
“…In support to the results of present study, the dietary saponin have been reported to have no significant effect on the carcass characteristics of broiler chicken (Zhang et al, ). Similarly, the decreased abdominal fat percentage due to supplementation of dietary saponins was reported in broiler chicken (Miah et al, and Afrose et al, ) and Muscovy duck (Jiang et al, ). However, in contrast to our results Zhang et al () did not found any significant difference in the abdominal fat of chicken due to supplementation of dietary mango saponins for 21 or 42 days.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, 100 ppm SE significantly reduced the only AST level when compared with the control group. Inconsistent with the present study, the lowering ability of saponins on serum cholesterol has also been reported for both human and animals [7,39,40] . Consistent with this study, Yang et al [41] observed that the green tea saponins had no effect on the serum cholesterol levels of broilers.…”
Section: Discussioncontrasting
confidence: 49%
“…Supporting to our results, in a lamb study, Brogna et al [48] observed that supplementing Quillaja saponin increased arachidonic acid (C20:4 ω6) and ω-3:ω-6 (LNA/LA) level of longissimus dorsi muscle but they did not observe any difference on SFA, MUFA and PUFA levels. Afrose et al [40] also, reported that Karaya saponin supplementation reduced saturated fatty acid levels due to the decrease in palmitic (C16:0) and stearic (C18:0) acids levels in the thigh and breast muscle of broilers. However they observed the total MUFA as well as PUFA were improved in response to treatment with Karaya saponin was primarily caused by the increase in oleic (C18:1) and linoleic (C18:1) acids levels in thigh and breast muscle.…”
Section: Discussionmentioning
confidence: 99%